The 2010 British Association of Stroke Physicians Survey of Interventional Treatments for Stroke in the United Kingdom. (October 2013) - Sanyal, R.; Barrick, J.; Bhalla, A.; Cassidy, T.; Collas, D.; Cloud, G.; Fearon, P.; Gompertz, P.; Keir, S.; Khanna, P.; Power, M.; White, P.; et al.
Introduction: The UK National Stroke Strategy (Department of Health 2007) states that patients should have access to a stroke service with neurointerventional capacity. This survey was conducted by the Clinical Standards Committee of the British Association of Stroke Physicians to get a snapshot of the availability of interventional treatments for stroke in the United Kingdom. Methods: Questionnaires covering availability of endovascular treatments for stroke, e.g. intra-arterial thrombolysis and mechanical thrombectomy, were emailed to all British Association of Stroke Physicians members in October 2010. Where more than one response was received from the same hospital, the data were only entered once. If there was a discrepancy between different respondents for the same hospital, details were cross-checked with the respondents to ensure accuracy. Results: Responses were received from 58 hospitals in England, Scotland, Wales, and Northern Ireland. Intra-arterial thrombolysis and/or mechanical thrombectomy were available in 23 hospitals. Of these, three had not performed any procedures in 2010. Twenty centres had conducted a mean (range) of eight (2–20) procedures during the 10-month period. Thirty-five hospitals were not offering endovascular treatments. Sixteen of these were not referring patients to centres which could provide interventional treatments. Hospitals offering endovascular treatments had a mean (range) of 5·2 (2–12) stroke physicians, 2·3 (0–4) interventional neuroradiologists, and 3·6 (0–9) noninterventional neuroradiologists. Only two hospitals providing interventions had four or more interventional neuroradiologists. Conclusions: Only a small number of hospitals in the United Kingdom provide interventional treatments for stroke. Almost 50% of hospitals not providing interventions had no processes in place for referral to providers.